Academic studies of the historian Ivan Mikhailovich Ionenko - P.S. Kabytov (Ученые записки Казанского университета: Серия Гуманитарные науки)
This paper summarizes the life and work of Doctor of History, Professor of Kazan State University Ivan Mikhailovich Ionenko (1913–1989), an outstanding Soviet historian and Honored Scientist of the Tatar Autonomous Soviet Socialist Republic. A list of sources necessary for reconstructing I.M. Ionenko’s biography was compiled. The stages of his life path were identified. The influence of changes in the historiographic situation of the second half of the 1950s and the discussions held during the 1960s was discussed. I.M. Ionenko’s participation in the activity of the Science Council on the Complex Problem “Great October Socialist Revolution” was analyzed. His role in the establishment and development of the Volga Section of the Science Council and the Regional Association of Agricultural Historians of the Middle Volga Region was shown. The focus of his research regarding the development of agricultural history, the Great Russian Revolution, and the Great Patriotic War was revealed. I.M. Ionenko’s work as the head of the Department of USSR History of Kazan University and as the founder of the scientific school was considered. It was concluded that a thorough analysis of the research activities of I.M. Ionenko, as well as reviews of his works, office documents, memoirs (those of him and his colleagues), and archive may contribute considerably to the study of the scholar’s biography.